2021
DOI: 10.1007/s11914-021-00656-0
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Lipidomics to Age-Related Musculoskeletal Disorders

Abstract: Purpose of Review The goal of this review is to highlight the need for new biomarkers for the diagnosis and treatment of musculoskeletal disorders, especially osteoporosis and sarcopenia. These conditions are characterized by loss of bone and muscle mass, respectively, leading to functional deterioration and the development of disabilities. Advances in high-resolution lipidomics platforms are being used to help identify new lipid biomarkers for these diseases. Recent Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…By utilizing bioinformatics methods, we identified that LEP, ADIPQO, RBP4 and DPP4 are associated with decreased skeletal muscle function. This discovery reinforces the conclusion that increased adipokine levels may have adverse effects on the physiological function of skeletal muscles [ 28 , 29 ]. Relationships between adipokines, skeletal muscle and bone metabolism are intricate.…”
Section: Discussionsupporting
confidence: 82%
“…By utilizing bioinformatics methods, we identified that LEP, ADIPQO, RBP4 and DPP4 are associated with decreased skeletal muscle function. This discovery reinforces the conclusion that increased adipokine levels may have adverse effects on the physiological function of skeletal muscles [ 28 , 29 ]. Relationships between adipokines, skeletal muscle and bone metabolism are intricate.…”
Section: Discussionsupporting
confidence: 82%
“…Among them, diacylglycerol (DAG) metabolic process and regulation of Notch signaling pathway might be remarkable. Recent lipidomics studies have shown significant dysregulation of lipids in aging-related bone mineral density loss and the occurrence of osteoporosis, including alterations in DAG [ 61 , 62 ]. In response to stimulations, activated phospholipase C (PLC) hydrolyzes PIP2 to DAG.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lipids play a role in lifespan regulation and age-related diseases ( de Diego et al, 2019 ). Very recently, the use of lipidomics to age-related musculoskeletal disorders was reviewed ( Mo et al, 2021 ). Siddharth et al (2017) monitored changes of serum lipids in aged mice with a sarcopenic phenotype and found that levels of LPC 20:5 and LPC 20:3 were reduced – although an explanation of the occurrence of these unusual fatty acids was not provided.…”
Section: Lysophospholipid As Inflammation and Disease Markersmentioning
confidence: 99%